పుట్టప్ప కథ - Sundaram, R.V.S. (Arkavathi Prakashana, 1975)
It's about the introduction of a legendry kannadiga writer K V Puttappa
Puttappa Katha
Keywords: Telugu; పుట్టప్ప కథ; Puttappa Katha; Literature; Telugu; Telugu